Efrem Syryjski, List do Publiusza - Szymczak, Tomasz (Vox Patrum, 2026)
This text contains a Polish translation of the Letter to Publius by Saint Ephrem the Syrian, together with an introduction. The text was first published—together with an English translation—only in 1976 by Sebastian Brock, who drew attention to its exceptional literary and theological value. Less than twenty years later, another English translation appeared, prepared by Edward G. Matthews Junior. The Letter to Publius, preserved in a single twelfth-century manuscript, belongs to the small number of surviving examples of Syriac artistic prose. The central motif of the work is the metaphor of the mirror, through which Ephrem reflects on the Last Judgment. The Gospel is presented as a mirror in which the human being recognizes the truth about himself, while one’s own conscience becomes the place of judgment, revealing both sins and good deeds. The text also contains an extensive list of Christological titles and a rich repertoire of rhetorical figures. Despite uncertainty regarding the identity of the addressee, the Letter to Publius constitutes an important witness to the theology, anthropology, and spirituality of Ephrem the Syrian.